IMPROVING THE METHODOLOGY FOR INTEGRATING BASIC AND CLINICAL SCIENCES IN MEDICAL EDUCATION - Xoliqova Oyistaxon Yuldashevna (Web of Journals Publishing, 2025)
This article provides an in-depth analysis of the methodological improvements required for integrating basic and clinical sciences in contemporary medical education. As the volume of medical knowledge expands, the traditional separation of pre-clinical and clinical phases becomes less effective. The study explores various integration models—horizontal, vertical, and spiral—and their impact on students' cognitive development. It highlights how an integrated curriculum facilitates the transition from theoretical knowledge to practical clinical application, enhancing students' diagnostic reasoning and professional competence. By moving away from the traditional "Flexnerian" model towards a unified, interdisciplinary approach, medical institutions can foster deeper conceptual understanding. The study emphasizes the role of case-based learning (CBL), team-based learning (TBL), early clinical exposure, and digital simulations in bridging the gap between biological sciences and patient care. The findings suggest that a coordinated methodological framework, supported by faculty development and innovative assessment tools, is essential for preparing future physicians to navigate the complexities of 21st-century healthcare.
Keywords: Medical education, integrated curriculum, basic sciences, clinical sciences, case-based learning, pedagogical methodology, clinical reasoning, vertical integration, spiral curriculum.